Dampak Pemberian Smartphone pada Anak Usia Dini terhadap Perilaku Sosial : The Impact of Early Smartphone Exposure on Young Children’s Social Behavior - Irnawati Nur Epatika Putri; Siska Putri Ayu (Litera Academica Publishing, 2025)
Early exposure to smartphones has become a growing concern as digital devices increasingly shape children’s daily activities and social interactions. This study aims to examine the impact of smartphone use among young children on their social and emotional development, particularly during the critical developmental phase known as the golden age. Using a literature review method, this article synthesizes findings from various empirical studies obtained through Google Scholar, focusing on both the positive and negative consequences of early smartphone use as well as the role of parenting patterns in mediating these effects. The review reveals that while smartphones can provide educational benefits and facilitate communication, excessive or unguided use tends to hinder children’s social interaction, reduce attention span, lower empathy, and disrupt emotional regulation. Many studies emphasize that limited face-to-face interaction caused by prolonged screen exposure negatively affects the development of children's social skills, self-confidence, and moral behavior. The discussion highlights that democratic and responsive parenting is crucial in guiding children toward healthy digital habits and minimizing harmful effects. It is concluded that parental supervision, appropriate usage limits, and early digital literacy education are essential to ensuring that technology supports rather than impedes optimal social-emotional development. These findings underscore the need for parents, educators, and policymakers to collaborate in fostering balanced and responsible digital engagement among young children.